Shades of Black. Assembling Black Arts in 1980s Britain. - Bailey, David A.; Baucom, Ian; Boyce, Sonia; Araeen, Rasheed; Piper, keith; Himid, Lubaina; Mercer, Kobena; pui san lok, susan; deSouza, Allen; Sedira, Zineb; Wilson, Judith; Bey, Dawoud; et al. (Durham : Duke University Press, 2005)
Sediran, Zineb ; Yong, Soon Min ; susan oui san lok ; Bailey, David A. ; Araeen, Rasheed
postcolonialisme, multiculturalisme, Groot-Brittanië
boek